PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Guterres, Luis Aparicio; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.03.TAHUN 2016, 2016)
urces that exist within a organization in addition to other resources of the organization. Basically,  an organization not only expect skilled human resources and skilled, but more importantly it expects its employees to work with enterprising and willing to achieve optimal results. This study aims to examine and analyze the influence of leadership style and work motivation on employee performance. This study was conducted in 02 State Public High School Baucau-Timor Leste. Using a sample of 58 teachers, the data collected using questionnaires and interviews. There are two types of data used in this study is qualitative and quantitative data, both derived from primary and secondary sources. The collected data were analyzed using descriptive analysis and multiple regression analysis. Based on regression analysis of the calculation results obtained conclusion, the influence of leadership style (X1) on teacher performance (Y) 0.571. The amount of motivation that directly influence on employee performance (Y) is 0,313. The magnitude of the effect of leadership style (X1) and motivation (X2) effect jointly by 73.5 percent while the remaining 26.5 percent is explained by other variables not included in this study.
Keywords: Style Leadership, Motivation and Performance Employees